Revitalization of Multicultural Values of Islamic Boarding Schools for Madrasas in Indonesia - Hakiemah, Ainun; Afifah, Farida Nur (Fahmina: Jurnal Pendidikan Islam, 2024)
This paper is motivated by the phenomenon of educators or policy holders who are dragged into the whirlwind of narrow and rigid transnational exclusive ideologies in the midst of the rampant growth of foreign educational institutions that are not rooted in Indonesian traditions as brought by transnational Islamic schools. In this case, the methodology of pesantren with its multicultural value is believed to be able to revitalize homogeneous mentality in madrasah institutions to produce friendly individuals and recognize diversity. Departing from this anxiety, this paper discusses three questions, first, what are the symbols and values in multiculturalism pesantren. Second, what is the urgency of the continuity of instilling the value of multiculturalism in Islamic boarding schools for madrasas. Third, what is the importance of revitalizing the values of multiculturalism of pesantren for madrassas in Indonesia. This research is a qualitative research with library research data collection techniques. The collected data will be reduced as needed and analyzed to obtain conclusions that are in accordance with the problems raised. The results of this research are first, multiculturalism pesantren must fulfill several elements such as kyai, santri, dormitory or cottage, mosque, yellow book and scientific transfer as the parent of Islamic education. Second, madrasas that have been the target of radicalism are very urgent to continue the value of multiculturalism as its parent, so that it is maintained from tranquility and peace and does not fall into modernity. Third, the revitalization of the values of multiculturalism in madrassas is important because the majority of pesantren are dominated by madrasah residents. The goal is to foster a sense of empathy and the value of equality in human relations, so that radicalism values can be overcome.